Circulating Type-1 Anti-Tumor CD4+ T Cells are Preferentially Pro-Apoptotic in Cancer Patients - Wesa, Amy K.; Mandic, Maja; Taylor, Jennifer L.; Moschos, Stergios; Kirkwood, John M.; Kwok, William W.; Finke, James Harold; Storkus, Walter J. (Frontiers in Oncology, 2014)
Melanoma patients frequently exhibit a deficiency in Type-1 (but not Type-2 or regulatory) CD4+ T cell responses against tumor-associated antigens (TAA), which may limit protection against cancer progression or responsiveness to immunotherapy in these individuals. Since such deficiency was acutely evident in patients with active disease, where chronic stimulation of anti-tumor CD4+ T cells would be expected and activation-induced cell death may be prevalent, we employed MHC Class II-peptide tetramers to characterize the frequency and apoptotic status of TAA- vs. influenza (FluM1) virus-specific CD4+ T cells in the peripheral blood of HLA-DR*0401+ patients with melanoma or renal cell carcinoma (RCC). We observed that Flu-specific CD4+ T cells ranged from 0.17 to 3.89%, while up to approximately 1% of CD4+ T cells reacted against individual TAA epitopes derived from the EphA2 or MAGE-6 proteins. The frequencies of EphA2 and MAGE-6-specific CD4+ T cells in patients were significantly correlated with active disease and patient gender (i.e. females > males), while frequencies of Flu-specific CD4+ T cells were distributed within a normal range in all patients. Notably, patient CD4+ T cells reactive with MHC class II-TAA (but not MHC class II-Flu) tetramers were significantly enriched for a pro-apoptotic (Annexin-V+) phenotype, particularly amongst the Th1 (T-bet+) subset. These results suggest that the preferential sensitivity of TAA (but not viral)-specific CD4+ Th1 cells to apoptosis in melanoma patients with active disease will need to be overcome for optimal clinical benefit of immunotherapeutic approaches to be realized.